New approach to evaluate late arm impairment and effects of dragon boat activity in breast cancer survivors. Issue 44 (November 2017) - Melchiorri, Giovanni; Viero, Valerio; Triossi, Tamara; Sorge, Roberto; Tancredi, Virginia; Cafaro, Domenico; Andreis, Caterina; Vulpiani, Maria Chiara; Saraceni, Vincenzo Maria
Abstract : Abstract: To verify the applicability of a new approach based on the strength curves (SCs) methodology in late arm impairment in breast cancer (BC) survivors and to evaluate the effects of dragon boat (DB) activity on the late regaining of the muscle strength, upper limb impairment, and quality of life in patients undergoing surgery for BC. Retrospective observational study on 64 subjects (54.5 ± 9.7 years), 47 of them had undergone unilateral mastectomy surgery and were evaluated for late arm impairment. A clinical evaluation of the shoulder and compilation of functional assessment (DASH, Rowe, Constant–Murley) and quality of life (SF-36) scales were carried out. Assessment of muscle strength with SC obtained with isometric assessments and serratus anterior muscle test were performed. Differences between the SC are evident between healthy and operated subjects. Among the 3 groups of operated subjects the difference in strength is maximum at 0°. Statistically significant difference was found between operated and nonoperated only in SF-36 scale. No significant difference was found between groups for shoulder instability and winged scapula. The SC can be used in the study of upper limb impairment after surgery for BC: measurements carried out at 1st degrees of the range of motion are more useful for clinicians. DB activity is useful to reduce the late arm impairment.